Determinant Of Faculty Of Islamic Economics and Business UIN SYAHADA Padangsimpuan In Transactions Using ZISWAF Sharing Application On Mobile Banking BSI - Nofinawati, Nofinawati; Sari, Indah; Siregar, Devi Srikandi (Journal of Islamic Financial Technology, 2022)
This research is a quantitative research using primary data and secondary data. Data collection techniques used are questionnaires and interviews. Sampling in this study used a random sampling technique with a total of 30 respondents. Data analysis used is validity test, reliability test, basic assumption test (descriptive analysis test, normality test, linearity test) classical assumption test (multicollinearity test, heteroscedasticity test) hypothesis test (t test, F test, R2 coefficient of determination test) and multiple regression test. To facilitate the process of analyzing the data of this research, it is assisted by the SPSS 23 program.The results of the t-test indicate that there is no partial effect of convenience on the use of the ZISWAF sharing application on BSI mobile banking, there is an influence of trust in the use of the ZISWAF sharing application on BSI's mobile banking, there is a beneficial effect on the use of the ZISWAF sharing application on BSI's mobile banking. Simultaneously, there is an effect of convenience, trust and benefits on the use of the ZISWAF sharing application on BSI mobile banking.